Evaluation of current community pharmacist practice in Saudi Arabia: A cross-sectional study from patients' perspective (PART I) - Abdulmajeed Bajuayfir; Mohammad Alhazmi; Omar Alshareef; Ahmed Rawas; Sumayyah Alsharif; Amal Almasoudi; Ejaz Cheema; Majid Ali (Wolters Kluwer Medknow Publications, 2023)
Objective: This study aimed to evaluate the current practice of community pharmacists from patients' and pharmacists' perspectives in Saudi Arabia. This paper presents the patients' perspective. Methods: A self-administered cross-sectional survey was developed to collect responses from patients in Saudi Arabia from February to April 2021. The questionnaire comprised several statements related to the best practice in community pharmacy. Patients' responses to each statement were scored using a 5-point Likert scale. Higher scores represented the greater extent to which the pharmacists perform the best practice in a community pharmacy setting and vice versa. Findings: The data of 233 participants were included in the analysis. The majority of the participants were female (67%) and Saudi nationals (96%). The minimum mean score was related to the statement: pharmacist discusses with you about herbal medications or vitamin supplements. The maximum mean score was related to the statement: Pharmacist explains to you about the dose of medications and when to take them. Participants who were <20 years old had a significantly highest mean score, whereas those above 40 years old had the least mean score, P = 0.001. Participants from the Eastern region had a significantly highest mean score, compared to South region participants who had the least mean score, P = 0.009. Conclusion: A gap in the current practice and the best practice of community pharmacists was found. The policymakers can utilize these findings to provide targeted professional development opportunities for the practicing community pharmacists to improve the overall service and care for the patients.